An atlas of immune cell exhaustion in HIV-infected individuals revealed by single-cell transcriptomics. Issue 1 (1st January 2020) - Wang, Shaobo; Zhang, Qiong; Hui, Hui; Agrawal, Kriti; Karris, Maile Ann Young; Rana, Tariq M.
ABSTRACT: Chronic infection with human immunodeficiency virus (HIV) can cause progressive loss of immune cell function, or exhaustion, which impairs control of virus replication. However, little is known about the development and maintenance, as well as heterogeneity of immune cell exhaustion. Here, we investigated the effects of HIV infection on immune cell exhaustion at the transcriptomic level by analyzing single-cell RNA sequencing of peripheral blood mononuclear cells from four healthy subjects (37, 847 cells) and six HIV-infected donors (28, 610 cells). We identified nine immune cell clusters and eight T cell subclusters, and three of these (exhausted CD4 + and CD8 + T cells and interferon-responsive CD8 + T cells) were detected only in samples from HIV-infected donors. An inhibitory receptor KLRG1 was identified in a HIV-1 specific exhausted CD8 + T cell population expressing KLRG1, TIGIT, and T-bet dim Eomes hi markers. Ex-vivo antibody blockade of KLRG1 restored the function of HIV-specific exhausted CD8 + T cells demonstrating the contribution of KLRG1 + population to T cell exhaustion and providing an immunotherapy target to treat HIV chronic infection. These data provide a comprehensive analysis of gene signatures associated with immune cell exhaustion during HIV infection, which could be useful in understanding exhaustion mechanisms and developing new cure therapies. GRAPHICAL ABSTRACT: